O Lugar, a presença e o tratamento dado às mulheres no livro didático da EJA: espaço negado, espaço reivindicado - Costa, Dalva de Oliveira (2011)
This study examined the treatment given to women in Textbook (LD) of Youth and Adults (EJA) and the legal system consisting of CF/1988 by LDBEN 9.394/96 and the PNE/2001, by the CNE / CEB / 2000 and the Hamburg Declaration: Agenda for the Future guiding public policy education for the area. Its relevance lies in its dual perspective: the withdrawal of the invisibility of women and the announcement of the visibility and appreciation of them. As for the methodological approach, this work fits the paradigm of qualitative research, whose analysis of the legal framework was performed using the technique of document analysis and content analysis. The analysis of the GT was based on the methodology recommended by the sociologist, researcher at the Centre Nationalde Recherche Scientifique (CNRS) of France, Andrée Michel in his book: "No stereotypes!: Overcoming sexism in children/s books and textbooks" . The survey results indicate that although the CF/88 represent a significant advance both in terms EJA, for equality of rights and duties between men and women, these advances are minimally maintained in the aforementioned corporate planning and even ignored in all of its operation, since when analyzing Chapter II The Basic Education - Section V - for Youth and Adults of LDBEN/96, it appears that there is a silence on the issue of gender on women. We come to the conclusion that this silencing is due to the removal of rights policy effected by the federal government, the neo-liberal orientation that through constitutional amendments, decrees and provisional measures, intervened in the process of processing and approval of LDBEN/96 and PNE/2001 of changing the CF/98, and this law has adapted to the dictates of the World Bank. For women in the textbook research showed small, but significant advances